Effects of intravenous rtPA in patients with minor stroke - Zhihao Lei; Shuanglin Li; Hongye Feng; Xiaohong Wu; Shiyu Hu; Jun Li; Gelin Xu; Lijie Ren; Suyue Pan (Annals of Medicine, 2024)
AbstractBackground Whether minor ischemic stroke (MIS) patients can benefit from intravenous thrombolysis (IVT) remains controversial. The association between the efficacy of IVT and baseline National Institute of Health Stroke Scale (NIHSS) score is unclear in MIS, while the association in moderate and severe stroke is known. This study aimed to explore the effect of IVT in patients with MIS and analyze its efficacy in patients with different baseline NIHSS scores.Methods Patients with a NIHSS score ≤5 within 4.5 h of stroke onset were screened in 32 centers. Patients with and without IVT were matched to a ratio of 1:1 with propensity scores. An excellent outcome was defined as a modified Rankin Scale (mRS) score ≤1 at three months after stroke onset. Safety outcomes included mortality and symptomatic intracranial hemorrhage (sICH). Multivariate analysis was used to compute the adjusted odds ratio (OR) for excellent outcomes. The effect of IVT was further analyzed in subgroups according to the baseline NIHSS score.Results Of the 23,853 screened, 3336 patients with MIS who arrived at the hospital within 4.5 h of onset were included. The 1163 patients treated with IVT were matched with 1163 patients without IVT. IVT in minor strokes generated an adjusted OR of 1.38 (95% CI: 1.09–1.75, p = 0.009) for excellent outcomes. There were no significant differences in mortality (0.17% vs. 0.09%, p = 1.000) and sICH (0.69% vs. 0.86%, p = 0.813) between patients with and without IVT. Subgroup analysis showed that there was no significant effect of IVT in the baseline NIHSS 0-1 or 2-3 subgroups, with adjusted OR of 0.816 (95% CI 0.437–1.53, p = 0.525) and1.22 (95% CI 0.845–1.77, p = 0.287), respectively. In patients with NIHSS score of 4–5, IVT was significantly effective, with an adjusted OR of 1.53 (95% CI 1.02–2.30, p = 0.038).Conclusion IVT can improve MIS outcomes. The risks of sICH and mortality did not increase, especially in patients with NIHSS scores 4 to 5, who could benefit from IVT significantly.